PENGARUH LATIHAN BEANBAG RELAY TERHADAP KECEPATAN LARI PADA PEMAIN SEKOLAH SEPAK BOLA (SSB) PCSS U-13 PEKANBARU - Putra, Yon Nasri Widodo; ', Ramadi; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: Based of the observation has done the researcher in the field to players SSB PCSS U-13 Pekanbaru, researchers found flaws in  the speed run at the time of the trial or official competition, when ball overtake long bait preceded often opponent until the ball with easy taken by opponent, conditions so would be demage to the team. Errors that occurred while overtake the ball one factor contributing to her is the players have not mastered the techniques the speed run is good and maximum. So it is not able to demonstrate achievement of the maximum for the team. The purpose of this study to determine the effect of exercise on Beanbag Relay for speed run to players SSB PCSS U-13 Pekanbaru.. In this study, researchers took population SSB PCSS U-13 Pekanbaru numbering 16 people. The sample in this research use sampling totality technique used is the full sample that is where all the population sampled. The instrument used to collect data is pree test and post test sprint run 100 yard. The results obtained from Pree test and post test in analisis with uji-t. Hypothesis testing results showed that thitung11,20 with ttabel 1,753 then Ha accepted, at the level of alpha (a) 0,05. It can be concluded that there is influence from Beanbag Relay to speed run for players SSB PCSS U-13 Pekanbaru. In this study, researchers took population SSB PCSS  U-13 Pekanbaru.